Pengaruh Stres Kerja Terhadap Produktivitas Kerja Melalui Motivasi : (Studi Kasus Pada Pedagang Grosir di Mall X) - Nabila Salsabila; Supardi Supardi; Agus Dharmanto (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research is aimed at measuring the direct and indirect effects of work stress on work productivity through motivation. This research implements quantitative research with the subject of wholesale traders who work at Mall The sequence used in this analysis is hypothesis testing using SPSS version 26 statistical tools. The results of the research state that the work stress variable partially influences work productivity with a calculated t value of 6,403 > 1.98217, work stress partially influences motivation with a calculated t value of 8,557 > 1.98217, motivation partially influences work productivity with a t value calculated 5,875 > 1.98217, and the indirect influence of work stress on work productivity through motivation has an influence with a total influence value greater than the direct influence value of 0.838 > 0.525.